The issue of plasma asymmetric dimethylarginine reference range - A systematic review and meta-analysis. - Balázs Németh; Zénó Ajtay; László Hejjel; Tamás Ferenci; Zoltán Ábrám; Edit Murányi; István Kiss (PLoS ONE)
Background Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase, marker and mediator of endothelial dysfunction. Several studies have demonstrated its value in cardiovascular risk stratification and all-cause mortality prediction. The aim was to determine the reference range of plasma ADMA in healthy adults. Methods and results Taking into account the most widely used ADMA measurement methods, only studies using either high performance liquid chromatography (HPLC) -with fluorescence or mass spectrometric detection-, or enzyme-linked immunosorbent assay (ELISA) to quantify plasma ADMA concentrations were enrolled. 66 studies were included in the quantitative analysis (24 using ELISA and 42 using HPLC) reporting a total number of 5528 non-diabetic, non-hypertensive, non-obese adults without any medication (3178 men and 2350 women, 41.6 ± 16.9 years old). The reference range of ADMA (in μmol/l with 95% confidence interval in parenthesis) was 0.34 (0.29-0.38)- 1.10 (0.85-1.35) with a mean of 0.71 (0.57-0.85) (n = 4093) measured by HPLC and 0.25 (0.18-0.31)- 0.92 (0.76-1.09) with a mean of 0.57 (0.48-0.66) (n = 1435) by ELISA. Conclusions Numerous publications suggested that asymmetric dimethylarginine is not only an outstanding tool of disease outcome prediction but also a new potential therapeutic target substance; the reference range provided by this meta-analysis can become of great importance and aid to further investigations. However, developing a standard measurement method would be beneficial to facilitate the clinical usage of ADMA.